Decreasing Total Hardness of Dug Well Water Against Variations in Boiling Time: Penurunan Kesadahan Total Air Sumur Gali Terhadap Variasi Lama Perebusan - Suseno; Naperta Bintaeka Saestri, Gisela (Jurnal Kimia dan Rekayasa, 2024)
Water is a basic needs for  humans, where one source of clean water is dug well. One of the problems that arise from dug wells is that water contains high hardness, when the water boiled it will cause a white crust on the bottom of the kettle or pan. This research aims to determine the level of the water in several wells owned by residents RT 1 RW 1 Mojosongo and to find out the decrease in hardness of well water with variations in the length of boiling water. This research refers to the analysis of hardness determination by complexometric method (SNI.06-6989.12-2004). After doing research on total hardness which is counted as CaCO3 the results are obtained : well A is 554,4 mg/l, well B is 567,6 mg/l, and well C is 580,8 mg/l. In variations of boiling 10 minutes, 20 minutes, 30 minutes, 40 minutes and 50 minutes for well water 1, 2 and 3, the total hardness results were below 500 mg/l as CaCO3 with an average decrease in total hardness respectively of 29 .07%; 42.51%; 57.62%; 64.34%; and 71.83%. The decrease in hardness by heating causing some calcium ions to precipitate as CaCO3 by releasing CO2 and H2O. AbstrakAir merupakan salah satu kebutuhan pokok bagi manusia, dimana salah satu sumber air bersih adalah sumur gali. Permasalahan yang timbul dari sumur gali salah satunya adalah airnya mengandung kesadahan yang tinggi dimana apabila air direbus menimbulkan kerak putih pada dasar ketel atau panci. Penelitian ini bertujuan untuk mengetahui tingkat kesadahan air di beberapa sumur milik warga Krajan Rt 1 Rw 1 Mojosongo dan untuk mengetahui penurunan kesadahan air sumur dengan variasi lama perebusan air. Penelitian ini mengacu pada analisis penetapan kesadahan total  dengan metode kompleksometri (SNI.06-6989.12-2004). Setelah dilakukan penelitian kesadahan total yang dihitung sebagai CaCO3 didapatkan hasil sebagai berikut : sumur A sebesar 554,4 mg/l, sumur B sebesar 567,6 mg/l, sumur C sebesar 580,8 mg/l. Pada variasi perebusan 10 menit, 20 menit, 30 menit, 40 menit, dan 50 menit terhadap air sumur 1, 2 dan 3 didapatkan hasil rata-rata penurunan kesadahan total secara berturut – turut sebesar 29,07%; 42,51%; 57,62%; 64,34%; dan 71,83%.